2022
DOI: 10.1101/2022.02.23.22271303
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in the quality of cancer care as assessed through performance indicators during the first wave of the COVID-19 pandemic in 2020: a Scoping Review

Abstract: Objectives: Summarize performance indicators used in the literature to evaluate the impact of the COVID-19 pandemic on cancer care (January-June 2020), and to assess changes in the quality of care as assessed via selected indicators. Methods: Scoping review. Indicators and their reported trends were collated following the cancer care pathway. Results: Database searches retrieved 6277 articles, 838 articles met the inclusion criteria, and 135 articles were included after full-text screening, from which 917 indi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 159 publications
(457 reference statements)
0
8
0
Order By: Relevance
“…The copyright holder for this preprint this version posted June 22, 2022. ; https://doi.org/10.1101/2022.06. 21.22276569 doi: medRxiv preprint a recent scoping review summarizing the impact of the pandemic on time to cancer diagnosis and treatment (8), a pre-pandemic perspective of the effect of lag time on oncologic outcomes among patients undergoing cancer screening, diagnosis, and staging is of paramount importance.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted June 22, 2022. ; https://doi.org/10.1101/2022.06. 21.22276569 doi: medRxiv preprint a recent scoping review summarizing the impact of the pandemic on time to cancer diagnosis and treatment (8), a pre-pandemic perspective of the effect of lag time on oncologic outcomes among patients undergoing cancer screening, diagnosis, and staging is of paramount importance.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…New and previously diagnosed cancer cases have been subject to risk-based prioritization and treatment triaging that differ from standard clinical practice (7). For cancers that were diagnosed in the first six months of the pandemic, an increasing trend in diagnosis of late-stage cancers and a decreasing trend in diagnosis of early-stage cancers were observed, as a reflection of the initial effects of extended lag times to diagnosis (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it enables the synthesis and communication of emerging evidence (30, 33) and the identi cation of knowledge gaps (35). This methodology has been described by the authors in two previous studies (36,37), where different clinical areas were studied. The PRISMA checklist -extension for scoping reviews (38) was used for reporting (Additional le 1).…”
mentioning
confidence: 99%
“…Based on a provider-based survey, the Japan Lung Cancer Society found that the number of newly diagnosed primary lung cancer patient decreased by 6.6% across 118 hospitals surveyed in January-October 2020 compared to the same period in 2019 (Japan Times, 2020 [46]). In the United Kingdom, a patient survey was conducted and found that of people with potential cancer symptoms, 45% did not contact their GP for their symptoms between March and August 2020 (Cancer Research UK, 2021 [47]).…”
mentioning
confidence: 99%